2016
DOI: 10.1111/eea.12499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of juvenile hormone and pyriproxyfen treatments on the production ofSpodoptera lituranuclear polyhedrosis virus

Abstract: Efficient production is essential for developing baculoviruses into marketable bioinsecticides. In this study, we evaluated how juvenile hormone (JH) III and the JH analog pyriproxyfen affected the production efficiency of Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) Nucleopolyhedrovirus (SpltNPV) in SpltNPV-inoculated early sixth instars. Both the JH III and pyriproxyfen treatments significantly enhanced the body size and weight of S. litura, which resulted in a 1.5-to 2-fold increase in the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…These results corroborated a previous report that showed treatment of H. armigera with exogenous JH increased HaNPV concentration 47 . Also, production of baculovirus occlusion bodies (OB) in Spodoptera lituralis larvae was increased following treatment with JH and pyriproxyfen 56 . According to this finding, we examined whether suppression of antiviral immunity by feeding on food containing fenoxycarb could affect susceptibility of H. armigera larvae to HaNPV.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results corroborated a previous report that showed treatment of H. armigera with exogenous JH increased HaNPV concentration 47 . Also, production of baculovirus occlusion bodies (OB) in Spodoptera lituralis larvae was increased following treatment with JH and pyriproxyfen 56 . According to this finding, we examined whether suppression of antiviral immunity by feeding on food containing fenoxycarb could affect susceptibility of H. armigera larvae to HaNPV.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also indicated that feeding on diet containing fenoxycarb for 48 and 96 h could increase the mortality of H. armigera larvae by HaNPV. There are two possible explanation for how JH could interfere with viral pathogenicity: first, fenoxycarb suppresses antiviral immunity and as a consequence virus have more opportunity for replication; and secondly, JH prolongs the larval stage and enhances feeding, thus leading to bigger larvae and higher virus yield 56 …”
Section: Discussionmentioning
confidence: 99%
“…The NPV mass production was influenced by several factors such as virus concentration, larval age at virus treatment, temperature, and harvesting time (Cherry et al 1997;Subramanian et al 2006;Rios-Velasco et al 2012). Furthermore, numerous techniques have been proposed to improve the production of baculoviruses such as juvenile hormones used for increasing the production of Spodoptera exigua multicapsid NPV (SeMNPV) (Lasa et al 2007) and for the production of Spodoptera litura NPV (SpltNPV) (Liao et al 2016). In addition, Elvira et al (2010) developed a low-cost diet for the large scale in vivo production of SeMNPV.…”
Section: Resultsmentioning
confidence: 99%
“…These assumptions are reflected in the following conditions on the parameters, a S ≫ a I , c S ≫ c I and d S < d I . In Table 1 we state units and numerical values for all model parameters based on published papers (Ball et al 2000;Ruiz-Nogueira et al 2001;Xiao and Van Den Bosch 2003;Dale 2006;Liu et al 2015;Liao et al 2016). While the techniques developed in this paper are independent of this special parametrization, the determined control strategies do depend on our chosen parametrization.…”
Section: Crop-pest-pathogen Systemmentioning
confidence: 99%